Case Report: ECMO rescue for cardiac arrest in a hyperthyroid patient triggered by COVID-19 infection - Ma, Shuaiting; Xie, Lutao; Lan, Pin; Wu, Haohao; Liu, Mingjun; Chen, Yi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronavirus disease 2019 (COVID-19) is a global pandemic, while both fulminant myocarditis (FM) and thyroid storm (TS) are life-threatening critical conditions. When these three conditions coexist in a single patient, the survival outcome can be severely compromised.Case introductionWe report a case of cardiac arrest in a hyperthyroid patient triggered by COVID-19 infection. The patient developed symptoms such as fatigue, chest tightness, and chest pain following SARS-CoV-2 infection, and experienced respiratory and CA en route to the hospital. Ultimately, the patient was diagnosed with FM and TS. The patient was treated with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) combined with continuous renal replacement therapy (CRRT). After hemodynamic stabilization, the patient received pharmacological management for arrhythmia control and hyperthyroidism, along with other symptomatic treatments. The patient eventually recovered and was discharged.ConclusionIn hyperthyroid patients infected with SARS-CoV-2, clinicians should remain vigilant for the potential development of FM and TS. VA-ECMO combined with CRRT represents an effective therapeutic approach in such critical scenarios.